PENDIDIKAN DAN KARIR PEREMPUAN DALAM PERSPEKTIF ISLAM - Nelsi Arisandy (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This paper discusses Islam views in women's education and career, by analyzing the verses and hadiths, and examine the history books can be concluded that Islam protects women's rights in education and a career. In the early development of Islam, women's education has not been made formally. It does not prevent Muslim women in his time became a reliable career women in their fields Among women who succeed in a career are Siti Khadijah, istreri Rasulllah. Thus, it can be said Islam does not prevent women to get an education and a career in accordance with the education obtained.